2021
DOI: 10.1002/marc.202100551
|View full text |Cite
|
Sign up to set email alerts
|

An AIE‐Active Ultrathin Polymeric Self‐Assembled Monolayer Sensor for Trace Volatile Explosive Detection

Abstract: This work has prepared polymeric self-assembled monolayer (SAM) sensors for the detection of trace volatile nitroaromatic compound (NAC) explosives by fluorescence quenching. A typical aggregation-induced emission (AIE) luminogen 1,1,2,2-tetraphenylethene (TPE) polymerizes into PTPE to increase the fluorescence intensity in the SAMs, and the phosphoric acid acts as the anchor group to form stable covalent bonds with the Al 2 O 3 substrate. This design takes advantage of the high sensitivity and good stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Interface defects can be eliminated by chemical bonding between anchors and the substrate, which could be evidenced by characteristic peaks at 1264 (stretching vibrations of C–N) and 1459 cm –1 (phenothiazine ring stretching vibrations) in the attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR, Figure a), , and the signals of the molecular characteristic elements, including Cl, N, P, and S, , in X-ray photoelectron spectroscopy (XPS, Figures b, S1, and S2) measurements. The covalent bonding could be further identified for the fitted fingerprint peaks at 533.0 eV assigned to In–O–P/PO, while the other two fitted peaks at 532.1 and 531.4 eV were originated from the ITO substrate (Figure c). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Interface defects can be eliminated by chemical bonding between anchors and the substrate, which could be evidenced by characteristic peaks at 1264 (stretching vibrations of C–N) and 1459 cm –1 (phenothiazine ring stretching vibrations) in the attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR, Figure a), , and the signals of the molecular characteristic elements, including Cl, N, P, and S, , in X-ray photoelectron spectroscopy (XPS, Figures b, S1, and S2) measurements. The covalent bonding could be further identified for the fitted fingerprint peaks at 533.0 eV assigned to In–O–P/PO, while the other two fitted peaks at 532.1 and 531.4 eV were originated from the ITO substrate (Figure c). ,, …”
Section: Resultsmentioning
confidence: 99%
“…243 As shown in Figure 17d, Ravoo et al found that the contact angle of arylazopyrazole SAM (184) could reversibly change under alternating UV and visible irradiation, confirming the reversible conversion of molecular conformations. 244 Furthermore, the contact angle can also be used to assess the in situ chemical reaction state by the surface wettability 245,246 and even infer the reaction mechanism. 247 Tang et al found that the contact angle of terthiophene SAM changed from ca.…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
“…As the number of nitro groups (electron‐withdrawing substituents) rises, their LUMOs decrease and the ability of nitroaromatic compounds to withdraw electrons improves, resulting in enhanced quenching efficiency with a detection limit as low as 0.07 ppm. Meanwhile, considering large specific surface area and high density of reaction sites of fibrous testing paper, Tang and coworkers [33] selected TPE as a unit to self‐assemble into monolayers on the Al 2 O 3 fibrous paper by in situ Suzuki polymerization, leaving a dense ultrathin polymeric PTPE monolayers to serve as sensors (Figure 4B, ii). The resulted PTPE‐coated testing paper showed high sensitivity for various NACs in a comparatively short time as shown in Figure 4B (iii).…”
Section: Photo‐induced Electron Transfer (Pet) ‐ Smart Sensingmentioning
confidence: 99%
“…For optical lighting, "AIE + Fiber" extends their functions from flexible lighting to remote optical transmission [28] and light diffusers, [29] which are inaccessible from the individual AIEgen alone. For smart sensing, "AIE + Fiber" sensors show advantages of higher sensitivity, [30] rapid response, [31] high spatial resolution, [32] and portability, [33] compared with those molecule-based sensors. For photodynamic and photothermal applications, "AIE + Fiber" amplifies their performance and expands applications in antibacterial protection, [34] hot therapy, [26] and seawater sterilization.…”
Section: Introductionmentioning
confidence: 99%